Work process in building construction : a case study of Kelantan Trade Center (KTC) - Mohd Afnan, Abdullah (2006)
In any construction industry, the work processes are very important in building construction. This is basic knowledge for implementation of construction. Each element of structure member has their advantage and disadvantage base on the need and the several of design for each building element. The information about work process in building construction need to clear in order to make the construction can be implementing without any intrude. The studies that be carried out is purpose to fulfill a few importance to become guideline for parties that involve in construction industry. Significance's of the study are to identify the method of process in building construction, so that the implementation of progress project can move smooth without problem. Besides that, preparation the reference material, also can be help to party that involve in construction industry to be more understand in method work process in building construction. In order to get the data, an interview, observation at site and video capture were be used to get all the information needed. The outcome from this study includes the work process for beam and slab, work process for column and also work process for wall of a building. Furthermore this study will be used as a future reference and also to increase the knowledge in work process in building construction.